2016
DOI: 10.1128/aem.03611-15
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Bdellovibrio bacteriovorus by Using the tdTomato Fluorescent Protein

Abstract: bBdellovibrio bacteriovorus is a Gram-negative bacterium that belongs to the delta subgroup of proteobacteria and is characterized by a predatory life cycle. In recent years, work has highlighted the potential use of this predator to control bacteria and biofilms. Traditionally, the reduction in prey cells was used to monitor predation dynamics. In this study, we introduced pMQ414, a plasmid that expresses the tdTomato fluorescent reporter protein, into a host-independent strain and a host-dependent strain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
2
29
0
1
Order By: Relevance
“…aeruginosa CFU numbers at time 24 hour might have been higher than that of the initial inoculation. A slight, but non-significant increase in cell viability after exposure to the predators seen in HaCaT, HepG2 and THP-1 cells, could also be as a result of individual predator cells remaining in the wells, as it was previously demonstrated that the predatory bacteria were able to attach to human corneal epithelial cells (HCLE) [35]. Our data supports earlier findings in which HCLE cells were exposed to high concentrations of B .…”
Section: Discussionsupporting
confidence: 90%
“…aeruginosa CFU numbers at time 24 hour might have been higher than that of the initial inoculation. A slight, but non-significant increase in cell viability after exposure to the predators seen in HaCaT, HepG2 and THP-1 cells, could also be as a result of individual predator cells remaining in the wells, as it was previously demonstrated that the predatory bacteria were able to attach to human corneal epithelial cells (HCLE) [35]. Our data supports earlier findings in which HCLE cells were exposed to high concentrations of B .…”
Section: Discussionsupporting
confidence: 90%
“…Heterologous promoters such as P nptII and P lac from E. coli, were used to express gfp (encoding green fluorescent protein) in B. bacteriovorus. Constitutive nptII promoter was proved to be functional in both, HD and HI growth phase (Mukherjee et al, 2015). Expression of gfp under inducible lac promoter was also observed in HD and HI strains (Flannagan et al, 2004;, but as noted by Flannagan et al (2004) it was independent of IPTG and could not be regulated.…”
Section: Genetic Tools For Modification Of B Bacteriovorusmentioning
confidence: 88%
“…Rather than its ability to form self-biofilm, it is the ability of BALOs to inhibit formation, as well as reduce preformed biofilms of other bacteria, that has raised general interest. Several methods have been developed to specifically study the role of predatory bacteria in biofilms; including fluorescently labeled B. bacteriovorus (Mukherjee et al, 2015), chip calorimetry assays measuring metabolic heat during biofilm removal (Buchholz et al, 2012), as well as atomic force microscopy for more mechanistic insight in biofilm formation and degradation (Núñez et al, 2005); the latter being limited to single-layered structures.…”
Section: Balos Regulation Of Prey and Non-prey Biofilmsmentioning
confidence: 99%
“…The resulting plasmid, pMQ578, and all plasmids made in this study are listed in Table 1. One variant of pMQ578 was made in which gfp was replaced with tdtomato from pMQ414 (15) using primers 4127 and 4218 and named pMQ643. For another, pMQ650, an artificial DNA sequence containing six restriction enzyme sites (EcoRI, SalI, BamH1, SpeI, SphI, and HindIII) and a sequence with stop codons in three frames was introduced using a 499 bp long double stranded DNA sequence listed as primer number 4068 (gBlock, IDT, Inc).…”
Section: Methodsmentioning
confidence: 99%